Cellular tracked optical wireless demonstration link - Parand, F; Faulkner, G; O'Brien, D (2003)
Line-of-sight optical wireless systems have the potential to provide extremely high bandwidth communications; the major problem is to ensure that a link can be maintained as transmitter and receiver more relative to one another, and to provide wide area coverage. Cellular systems, or tracking systems that incorporate multiple sources and detectors, have the potential to achieve high bandwidth and provide the necessary area coverage. In the paper, the construction and testing of a cellular tracked demonstration optical wireless link that empl'oys a 3 × 3 array of vertical-cavity surface-emitting lasers in the transmitter and a 3 × 3 array of silicon photodiodes in the receiver is reported. The link operates at 32.77 Mbit/s and is demonstrated to provide coverage to a BER of 1 × 10-9 across an area of 0.8 m × 0.8 m at a link distance of 2.5 m. This is believed to be the first reported cellular tracked link that demonstrates tracking in two dimensions. Consideration is given to extending the coverage area of the link.